Description of a new species of Odonaspis Leonardi (Hemiptera: Coccomorpha: Diaspididae) from Australia - Ben-Dov, Yair (Zootaxa, 2015)
The adult female of Odonaspis bouldersensis Ben-Dov, new species, collected in the Boulders National Park, Queensland, Australia, off a species of Poaceae, is described.